DEVELOPMENT OF BUSINESS STRATEGIES TO INCREASE SALES TURNOVER OF AGRICULTURAL MECHANIZATION EQUIPMENT WITH THE QSPM METHOD AT PT GOLDEN PRATAMA GEMILANG - Pratama, Okky Aditya; Tambunan, Damelina Basauli (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to formulate marketing strategies for PT Golden Pratama Gemilang (GPG) to increase the sales turnover of agricultural mechanization tools by employing the SWOT approach and the Quantitative Strategic Planning Matrix (QSPM) method. The research utilizes a qualitative method by collecting data through in-depth interviews, document analysis, and direct observations. The SWOT analysis revealed that PT GPG’s strengths include a strong company reputation, high-quality products meeting international standards, effective after-sales services, robust relationships with key clients, and efficient product demonstrations. However, the company faces weaknesses such as relatively high product prices, limited promotional capacity, and challenges in workforce regeneration. External opportunities identified include agricultural modernization policies, growing demand for mechanization, strategic partnerships with state-owned enterprises (BUMN) and private sectors, and advancements in mechanization technologies. Conversely, major threats include price competition from local competitors, macroeconomic challenges, insufficient market education, and negative perceptions of consumable parts. Through QSPM analysis, strategies with the highest Total Attractiveness Scores (TAS) were prioritized for implementation. The top-priority strategy identified is collaborating with local Original Equipment Manufacturers (OEMs) to reducethe cost of consumable parts, which achieved the highest TAS value. Other prioritized strategies include offering flexible payment options to small and medium-scale farmers, developing products tailored to specific land needs, and collaborating with the Ministry of Agriculture to promote agricultural modernization. The findings of this study emphasize the importance of a systematic approach in formulating marketing strategies. The proposed strategies are expected to assist PT GPG in enhancing competitiveness,expanding market share, and achieving sustainable sales growth in the agricultural mechanization industry.